Multicenter Surveillance of Capsular Serotypes, Virulence Genes, and Antimicrobial Susceptibilities of Klebsiella pneumoniae Causing Bacteremia in Taiwan, 2017–2019 - Liao, Chun-Hsing; Huang, Yu-Tsung; Hsueh, Po-Ren (Frontiers in Microbiology, 2022)
We conducted a longitudinal epidemiological surveillance of hypervirulent Klebsiella pneumoniae (hvKP) in Taiwan. Bacteremic KP isolates collected from 16 hospitals in Taiwan between 2017 and 2019 were collected, and the virulent serotypes (K1, K2, K20, K54, and K57), antimicrobial susceptibilities, and virulence genes of these isolates were investigated. During the 3-year period, 1,310 bacteremic KP isolates were collected, of which 27.5% belonged to virulent serotypes, including K1 (n = 162), K2 (n = 74), K57 (n = 56), K54 (n = 41), and K20 (n = 27). K1 was the most prevalent capsular serotype, with an annual prevalence of 11–15%, and was equally distributed across the four geographic areas. The prevalence of K2 declined significantly in 2019. According to wzi-K typing results, 87% of K1 isolates were classified as wzi-1. Among K2 isolates, wzi-72 (55.4%) and wzi-2 (41.9%) were the most common, whereas wzi-206 was the most prevalent (48.2%) among K57 isolates, followed by wzi-77 (25.0%). Wzi-115 accounted for 85.4% of the K54 isolates, whereas wzi-95 accounted for 92.6% of K20 isolates. rmpA was present in 99.4% of K1, 98.6% of K2, 89.3% of K57, 78.0% of K54, and 84.0% of K20 isolates. rmpA2 was present in 100% of K1 and 98.6% of K2 isolates but was only present in 64.3% of K57, 58.5% of K54, and 74.1% of K20 isolates. K1 remains the dominant hvKP serotype and is associated with most virulence genes in Taiwan. Further studies are required to elucidate the significance of other virulent serotypes.